2003
DOI: 10.1007/978-0-387-35692-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Internet Marketing Communications: Interactivity and Integration

Abstract: Abstract:This paper reports exploratory research into the role of the Internet in marketing communications and the conceptualisation of integration and interactivity in this context. Three mini case studies of large companies in the fast moving consumer good industry illustrate the application of frameworks developed for the understanding of integration and interactivity. The case studies show uncertainty about the value of the Internet as a communications channel and the use of interactive tools. The more adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the inherent preference that users have to the diffused information (product, brand, etc.) is also a factor that determines the activations (Lawton and Gregor 2003). To account for this factor, we extend IC accordingly, by associating each user w with a random variable h w that follows the Beta distribution h w $ Betaða; bÞ and characterizes the resistance of the user to become activated in the presence of social influence.…”
Section: Independent Cascade Modelmentioning
confidence: 99%
“…However, the inherent preference that users have to the diffused information (product, brand, etc.) is also a factor that determines the activations (Lawton and Gregor 2003). To account for this factor, we extend IC accordingly, by associating each user w with a random variable h w that follows the Beta distribution h w $ Betaða; bÞ and characterizes the resistance of the user to become activated in the presence of social influence.…”
Section: Independent Cascade Modelmentioning
confidence: 99%
“…The first three goal categories represent within-person goals, and the last three categories represent goals with respect to the relationships between people and their environments (Lawton & Gregor, 2002). Figure 1.…”
Section: Learning For Enjoymentmentioning
confidence: 99%
“…Forrester and Jantzie (2004) proposed that multimedia allows instructors and designer to bring the real world to the learners through the use of audio and visual functions. Lawton and Gregor (2002) analysed the uses of Internet interactivity for marketing and suggested that in the Internet environment, non-passive, user-pull, and interactive tools have the greatest potential to add value.…”
Section: Adoption Of Multimedia and Interactive Technologiesmentioning
confidence: 99%